ANALISIS YURIDIS TERHADAP KETENTUAN LIMITASI WAKTU DALAM PENYIDIKAN TINDAK PIDANA PILKADA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2015 JO UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PEMILIHAN GUBERNUR BUPATI DAN WALI KOTA - Juwita, Annisa; Indra, Mexsasai; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The process of resolving criminal offenses was carried out through the Sentra Gakkumdu forum. The Integrated Law Enforcement Center (Gakkumdu) consists of the Republic of Indonesia Bawaslu, the Republic of Indonesia National Police and the Indonesian Prosecutor's Office. The period of the investigation and prosecution process that is too short can cause the perpetrators of election crimes to avoid legal proceedings. Certainly this will greatly injure the value of justice in the law itself. Efforts to achieve substantive justice and electoral justice are limited by procedural justice alone. This certainly has an impact and a bad precedent for the enforcement of criminal acts of regional elections.What is the juridical analysis of the provisions of the time limit in the investigation of election criminal acts based on Law Number 1 of 2015 Jo Law Number 10 of 2016 concerning Election of Governors, Regents and Mayors who discuss protection? How to manage the future? How do you set the term of office? Absorption of Pilkada criminal acts based on Law Number 1 of 2015 Jo Law Number 10 of 2016 concerning Election of Governors for Regents and Mayors?Theories used in this research include justice theory and court legal policy theory. This type of research can be classified in normative legal research, namely legal research conducted by examining library materials. This study examines the subject matter in accordance with the scope and identification of problems through a statute approach carried out by examining the legislation and regulations relating to the legal issues under study.The conclusion that can be obtained from the results of the study is the limitation of time provisions in the investigation of criminal acts of elections that are regulated in Law Number 10 of 2016 concerning the Election of Governor of Regents and Mayors is still not clearly regulated. The process of enforcing the law against the crime of regional elections has not provided a sense of justice for the people.. The provisions of a brief investigation must be harmonized with a quick and short trial process. Related to several cases that have expired, it becomes a reference for law enforcement officials so that in the future they will be more professional in carrying out the investigation process.Keywords: Limitation of Time, Investigation, Crime of Election